Descriptions of two new freshwater neotropical species of Rhinebothrium (Cestoda: Rhinebothriidea) from Potamotrygon motoro (Chondrichthyes: Potamotrygonidae) - Menoret, Adriana; Ivanov, Verónica A (Folia parasitologica, 2011)
Two new species of Rhinebothrium (Cestoda, Rhinebothriidea) from potamotrygonid stingrays in the Neotropical region are herein described, which raises the total number of Rhinebothrium species known from Neotropical freshwaters to five. Rhinebothrium corbatai sp. n., and Rhinebothrium mistyae sp. n. were both collected from Potamotrygon motoro (Müller et Henle), captured in four tributaries of the Paraná River in Santa Fé Province, Argentina. The new species can be distinguished from their congeners, and from each other, by a combination of various features, including worm size (length and number of proglottids), number of loculi per bothridium, microthrix pattern, size of the cirrus sac, and the extent of the vas deferens. The discovery of these new species from P. motoro supports the pattern of high host specificity in this cestode genus, and reinforces the notion that some of the previous records of the enigmatic R. paratrygoni may correspond to new species of Rhinebothrium yet to be described.
Keywords: druhová specificita; rejnokovití; cestodózy; Animals; Fresh Water; nemoci ryb; Cestode Infections; zvířata; Fish Diseases; Species Specificity; sladká voda; Cestoda; Skates, Fish